(3GdefKhQGJ hYjhf GdeSGFd GdegeGJs - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3YeQ Hf YKeGf Hf MSf GdTgjQ HGdHSJGf GdTGaYi s)
(3ChdgG (B:s
(3CeG HYO abO GSJNQJ Gddg GdYXje ai JQJjH GdaJGhi GdJi dTjNi CHj RcQjG jMji Hf TQa GdfhGhi s
(3BNQgG (B:s
(3hde fUH MhGdi GdbHQ Ce dG CLGH QVi Gddg Yfg gPG eTghQ ai cJH GdQbGFb hGddg CYde s
(3hdYdgG aJGhGg GdUZQis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B149 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B202s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1859s
Keywords: (3Gdabg GdTGaYjs